Attractive ellipsoids based robust control design of switched systems: A geometrical approach (2016)
This contribution deals with a robust control design for general switched affine control systems. Dynamical models under consideration are described by ordinary differential equations involving a switching mechanism and in the presence of bounded uncertainties. The design procedure we analyse is based on the newly elaborated attractive ellipsoids method ([33]). The stability and robustness of the resulting closed-loop system involves an abstract Clarke stability theorem. A short discussion on the obtained analytic results and possible applications and extensions is also included. © 2016 IEEE.